Retraction Notice - Ahmad, Akram (Journal of Pharmacy Practice and Community Medicine)
The research article entitled “Vannala V, Balachandar, Kumaran K, Sigamani R. Biofilm formation on polytetrafluoroethylene coated versus uncoated brackets in a South Indian Population. Journal of Pharmacy Practice and Community Medicine. 2017;3(3):188-90. doi:10.5530/jppcm.2017.3.38 is retracted.[1] JPPCM received an email from the corresponding author, who asked if there was a way to edit or amend or withdraw the article that was previously published in JPPCM.